The intensity and duration the movement of formation waters from marginal collectors tolbachinskii suite (Proceedings of Voronezh State University. Series: Geology, 2017)
Data field's tube "International", the General hydrogeological characteristics of brines tolbachinskii Suite. Considered the intensity and duration of the movement of highly mineralized formation water in marginal composed of fractured dolomite reservoirs tolbachinskii Suite. The results obtained indicate about the dependence of the spout of highly mineralized formation waters from a structural-tectonic and lithological-facial features of water-bearing rocks. It is established that the changing intensity of water inflow to wells due to the peculiarities of the structure of hydrous collectors tolbachinskii Suite with extremely low parameters of conductivity and extremely low stocks the natural high-pressure high-mineralized produced waters and brines.
Keywords: Nepsko-Botuobinskaya antecline; Mirny ledge; field tubes; Tolbachinsky entourage; marginal fractured reservoirs; saline water; saturated brines of calcium chloride composition